Numerical study on ion migration in concrete under the influence of salt solution - Xianyuan Chen; Zhaocai Meng; Xinjiang Zheng; Zirui Gao (Scientific Reports)
Abstract This study investigates the migration and distribution of sulfate and chloride ions in concrete, incorporating the time-dependent relationship between the concrete compaction process and ion migration. Based on Fick’s second law, a modified model for sulfate ion migration in concrete is established. The findings reveal that the sulfate ion concentration within concrete increases with time but at a decreasing rate, with the compaction process significantly affecting this growth. The distribution of sulfate ions shows a decrease with increasing depth, and the difference between the modified model and the diffusion model amplifies over time. The external ion concentration has a minor impact on the distribution pattern but affects the internal ion concentration. Additionally, the study indicates that cracks initiate within 30 mm of the concrete surface and extend with time, leading to structural degradation. The pore compactness process has a limited effect on chloride ion content, which remains relatively stable before concrete deterioration.